Photochemical enrichment of dissolved organic matter from different soils of a tidal river basin: significance to estuarine carbon cycle - Zhou, Yuping; Zhu, Yuxuan; Jiang, Sen; Meng, Di; Pang, Yu; Xiao, Yihua (Frontiers in Marine Science, 2024)
Eroded soils sustain a substantial part of organic matter in tidal rivers adjacent to estuaries, and photochemical transformations of soils in tidal rivers would influence estuarine elemental cycles. However, complex aquatic environments and diverse soil sources complicate the enrichment of dissolved organic matter (DOM) photoreleased from soils. Here, we conducted a 7-day irradiation experiment for seven kinds of soils from the lower basin of Dagu River (DGR) in the laboratory to study the influence of salinity and soil properties on DOM chemistry by characterizing the content and optical properties of DOM. Results showed that light cultures had higher amount of DOM and humic-like components than dark cultures. Principal component analysis (PCA) and Mantel’s analysis found that salinity and soil properties significantly influence the production of photoreleased DOM, especially humic-like components. Salinity could inhibit the photodissolution of soils, and aged soils with low δ13CSOM released more DOM and humic-like components. Although the DGR is impacted by intruded seawater, high content of photoreleased DOM in seawater cultures still pointed out the important contribution of soil photodissolution to the DOM reservoir of tidal rivers. Considering high proportion of humic-like components in photoreleased DOM, photochemical transformations of soils in tidal rivers would promote the export flux of carbon from estuaries to open seas. This study emphasizes the importance of soil photodissolution of tidal rivers in the carbon transfer from lands to oceans.